Evaluasi Sistem Perawatan Pada Mesin Winding Menggunakan Metode Overall Equipment Effectiveness - Leo Radinius Ndruru; Edi Sumarya; Annisa Purbasari (Jurnal Teknik Ibnu Sina, 2026)
The decline in the effectiveness of the winding machine at PT Rubycon Indonesia reduces the productivity and quality of capacitors. The average downtime reaches 140 minutes per day with an OEE of 81%, below the world-class standard of 85%. This study aims to identify the causes of low machine effectiveness and implement improvements through OEE and Six Big Losses analysis. The method used is a quantitative and qualitative approach based on production data and six months of observations (July–December 2024). The analysis is carried out through OEE components (availability, performance, quality), Six Big Losses, and supported by Pareto and fishbone diagrams. After identifying the root cause, corrective actions are taken to reduce breakdowns and optimize the performance of the winding machine. The results show that the average OEE value after the improvements was 86%, indicating that the improvements have a positive impact on machine efficiency and performance. However, regular monitoring and maintenance are still required to maintain stable performance.